Despite the Odds : The Contentious Politics of Education Reform - Grindle, Merilee Serrill (Book collections on Project MUSE., 2004)
'Despite the Odds' examines five examples of education reform in South America, focusing on the political battle to secure reform in the face of powerfully entrenched opposition. It shows how strategic choices by reformers can reshape power equations & undermine institutional biases.